First make it

\(6x^2-x-2<0 \)

Then factor

\((3x-2)(2x+1)<0\)

Then solve if the inequality was an equality

Then add the inequality back in

x (the wired e sign) (-1/2,2/3)

hope this helps :)

minus 5x on both sides

2y=-5x-9

divide by 2

y=-5/2x-9/2

in format, y=mx+b

-5/2 is the m here

so

\(\frac 5 2\)

x=-73/25

y=1 6/25

z=1/10

oof wasnt right

yikesss

Its probably:

In triangle ABC, *idiot forgets to copy latex*

I can think of the first one off the top of my head, 5+6i This is because of difference of squares formula, (a+b)(a-b)=a^2-b^2 hope this helps a bit even if i didnt solve the whole thing

stop being toxic fam

the whole point of this is to create solutions to help other people understand

not cool

also if you wanna say tht sign in first

no 🏀's

?

who are you

wait who r u

btw u sniped meh

i got this

12 months (like in jail, punishment)

upvotes pls